A convenient access to the tricyclic core structure of hippolachnin A. Issue 1 (6th January 2016) - Datta, Ritabrata; Dixon, Ryan Joseph; Ghosh, Subrata
Graphical abstract: Abstract: A concise route for the synthesis of the enantiopure oxacyclobutapentalene core structure present in hippolachnin A has been developed. The key steps involve ring closing metathesis to construct butenolide and its intramolecular [2+2] photocycloaddition.